Sistem Pemasaran Beras Bujang Marantau Di Kecamatan Sungai Tarab, Kabupaten Tanah Datar, Provinsi Sumatera Barat - Alviedo; Kilat Adhi, Andriyono; Rosiana, Nia (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
The “Bujang Marantau” rice variety is local rice from Tanah Datar Regency which was registered as a national superior rice variety by BPTP West Sumatra in 2015 and grows well in Tanah Datar Regency. This increase in “Bujang Marantau” rice production must be balanced with a good marketing system so that farmers and institutions marketing can receive more favorable prices. The study is aimed to analyze the channels, functions and operational efficiency of rice marketing (marketing margin, farmer’s share, and profit to cost ratio) in Sungai Tarab District. This research involved 45 farmers as samples obtained through a simple random sampling method. Marketing institution respondents were obtained using the snowball method based on the flow of information from farmers and 15 marketing institution respondents were obtained. Qualitative data is used to analyze marketing channels and institutions. Quantitative data is used to analyze marketing margin, farmer’s share, profit to cost ratio and marketing efficiency index. The results showed that there are 3 marketing channels and 3 types of marketing institutions involved. The results of the marketing operational efficiency analysis show that the relatively efficient marketing channel is channel III because it has the lowest marketing margin value, the highest farmer’s share, and the shortest marketing channel compared to other channels. Marketing institutions should further optimize the marketing functions of each institution, such as the transportation function, so that transportation costs can be lower and minimize marketing costs more efficiently.